2022
DOI: 10.5751/es-12887-270111
|View full text |Cite
|
Sign up to set email alerts
|

Operationalizing agency in livelihoods research: smallholder farming livelihoods in southwest Ethiopia

Abstract: Livelihoods are activities and practices in which social and environmental factors interlink, and they play a key role in achieving human well-being and environmental conservation. Livelihood analyses are therefore important to social-ecological systems research. With a few exceptions, however, the concept of agency has been largely missing in research applying the social-ecological systems approach. This is an important gap to address, because humans are not passive victims of broader sociopolitical trends an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 34 publications
0
7
0
Order By: Relevance
“…Specialization was measured by Simpson's index based on ecosystem service production data, and telecoupling by a combination of ecosystem service production data and weighted average ecosystem service flow data. Biophysical conditions (such as altitude and forest cover) and limited tenure security and use rights in the study area may restrict smallholders' agency to change their ecosystem service production, especially if they belong to poor or already vulnerable groups , Manlosa 2022). Kebeles at lower, coffee-suitable altitudes did not exploit comparative advantages as much as kebeles at higher altitudes.…”
Section: Comparative Advantage Altitude and Their Interaction Influen...mentioning
confidence: 99%
See 2 more Smart Citations
“…Specialization was measured by Simpson's index based on ecosystem service production data, and telecoupling by a combination of ecosystem service production data and weighted average ecosystem service flow data. Biophysical conditions (such as altitude and forest cover) and limited tenure security and use rights in the study area may restrict smallholders' agency to change their ecosystem service production, especially if they belong to poor or already vulnerable groups , Manlosa 2022). Kebeles at lower, coffee-suitable altitudes did not exploit comparative advantages as much as kebeles at higher altitudes.…”
Section: Comparative Advantage Altitude and Their Interaction Influen...mentioning
confidence: 99%
“…These considerable potential positive and negative consequences of specialization require informed decisions regarding land use and ecosystem services. The role of farmers in land governance in our study area is limited, and is for example restricted by limited tenure security and land use rights , Manlosa 2022. Governance related to ecosystem service management is often strongly hierarchical, and dominated by government administrative organizations, which can lead to power capture, where the interests of few powerful stakeholders override those of smallholder farmers (Jiren et al 2018(Jiren et al , 2022.…”
Section: Implications For Policy Makingmentioning
confidence: 99%
See 1 more Smart Citation
“…The first category is to analyze the level of livelihood resilience from a subjective perspective using methods such as fuzzy integrated evaluation, hierarchical analysis, and expert evaluation. Manlosa (2022) use a study of smallholder livelihoods and food security in southwestern Ethiopia as an example to construct a conceptual analytical framework for livelihood resilience that includes four institutional pillars: preconditions, processes, power, and possibilities. Nath et al (2020) found that various variables related to conflict and rulemaking would affect the level of livelihood resilience of residents in Bangladesh's paddock.…”
Section: Introductionmentioning
confidence: 99%
“…One of the theoretical frameworks guiding this study is the Sustainable livelihood framework particularly human and social capital assets on improving livelihoods outcomes of farmers through adopting digital technology in accessing markets. Livelihood analyses have made important contributions to broader research areas such as those concerned with development, the environment, and sustainability (Manlosa 2022). This review articulates accessing markets, financial services using digital technology tools and proper digital infrastructure can improve household food security through improved incomes.…”
Section: Introductionmentioning
confidence: 99%